2013
DOI: 10.5012/bkcs.2013.34.5.1383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thiol Molecular Backbone Structure on the Formation and Reductive Desorption of Self-Assembled Aromatic and Alicyclic Thiol Monolayers on Au(111) Surface

Abstract: The surface structure and electrochemical behavior of self-assembled monolayers (SAMs) prepared from benzenethiol (BT), cyclohexanethiol (CHT), and cyclopentanethiol (CPT) on Au(111) surface were examined by scanning tunneling microscopy (STM) and cyclic voltammetry (CV) to understand the influence of thiol molecular backbone structure on the formation and reductive desorption behavior of SAMs. STM imaging showed that BT and CPT SAMs on Au(111) surface formed at room temperature were mainly composed of disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The simple behavior observed for the reductive desorption of alkanethiol SAMs becomes more complex when aromatic or heterocyclic thiols are included in the same analysis since they have different S-Au bond strength [29], intermolecular forces dominated by π-π interactions, different surface coverage, and accordingly different surface structures [30]. In general they exhibit more positive E p values than those found for alkanethiol SAMs, a fact that has been associated with the aryl group that withdraws electrons from the Au surface easier than the aliphatic chains, thus favoring reductive desorption [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple behavior observed for the reductive desorption of alkanethiol SAMs becomes more complex when aromatic or heterocyclic thiols are included in the same analysis since they have different S-Au bond strength [29], intermolecular forces dominated by π-π interactions, different surface coverage, and accordingly different surface structures [30]. In general they exhibit more positive E p values than those found for alkanethiol SAMs, a fact that has been associated with the aryl group that withdraws electrons from the Au surface easier than the aliphatic chains, thus favoring reductive desorption [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In this sense, there are two experimental characteristics that are important to consider. First the aromatic thiols have smaller θ values than the aliphatic ones (Table 1), and it is known from STM data that they form more disordered SAMs [31]. On the other hand, it has been shown that the structural order of aromatic thiol SAMs on Au(111) can be considerably enhanced by increasing the number of phenyl rings in the molecular backbone [66][67][68] and by inserting the alkyl spacer between the phenyl ring and the sulfur…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is even possible to exercise electrochemical control over the formation of adlayers at SS interface. 16 The repair of defects in self-assembled layers at the SS interface can be promoted if there is a dynamic exchange between molecules on the surface and in the solution phase. 8,17 Different areas of technology and science profit from temperature dependent SS interface studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetry blocking experiments provide meaningful information regarding the electron-transfer properties of SAMs, which are significantly influenced by the formation and surface structural characteristics of monolayers. [35][36][37][38][39] Figure 2 displays cyclic voltammograms of bare Au and PSC SAM-covered Au electrodes. The PSC SAM-covered Au electrodes were obtained by soaking the Au electrode in a 0.01 mM ethanolic solution of PSC at 323 K for 2 h. The peak currents was 22.0 μA for the bare Au electrode and 13.8 μA for the PSC SAM-covered Au electrode.…”
mentioning
confidence: 99%